Stem cells and exosomes: as biological agents in the diagnosis and treatment of polycystic ovary syndrome (PCOS) - Hadidi, Mahta; Karimabadi, Keyvan; Ghanbari, Elham; Rezakhani, Leila; Khazaei, Mozafar (Frontiers in Endocrinology, 2023)
A typical condition of the female reproductive system is polycystic ovary syndrome (PCOS). Hyperinsulinemia, insulin resistance, obesity, and hyperandrogenism are just a few of the metabolic abnormalities linked to this disease. Type 2 diabetes, hypertension, and cardiovascular disease are further issues related to PCOS. One consequence of this syndrome for which numerous treatment procedures have been developed is infertility. Metformin and clomiphene, two common allopathic medications used to treat PCOS, both have drawbacks and are ineffective. It is vital to seek novel therapeutic modalities to address these constraints. Exosomes (EXOs) are a particular class of extracellular vesicles that cells release, and they are known to play a significant role in mediating intercellular communication. A wide range of cargo, including lipids, proteins, mRNA, miRNAs, and numerous other noncoding RNAs, are contained in the nanoscale lipid bilayer exosomes. The cytokine effects of stem cells and EXOs derived from them enable the defense against metabolic diseases like PCOS. Moreover, EXO microRNAs can potentially be employed as biomarkers in the detection and management of PCOS. In this study, the potential of stem cells and exosomes are specifically investigated in the diagnosis and treatment of PCOS as one of the diseases of the female reproductive system.